The Line of Fit towards ASEAN Connectivity: Focus on the Philippine Political Structure and Processes - J. AGUJA, HILTON (Jurnal Studi Pemerintahan, 2016)
The Hanoi Declaration on the adoption of the Master Plan on ASEAN Connectivity was adopted on 28 October 2010. It calls for a well connected ASEAN in line with the vision to put in place an ASEAN Community by 2015. The Declaration speaks of a three pronged approach for the achievement of the envisioned connectivity: Physical connectivity, that is, to connect ASEAN through enhanced physical infrastructure development; Institutional connectivity, that is, effective institutions, mechanisms and processes and; People to people connectivity for an empowered people across the region.The concern of this paper focuses on institutional connectivity that is basically anchored on the political component of the Master Plan. As it stands, various issues currently exist as ‘impediments to movement of goods, services and skilled labor across borders’. Needless to say, these issues are policy concerns requiring political decisions that hinge on the political sphere of every member country. It is on this point that this paper derives its relevance. In this regard, the paper argues for some fundamental restructuring to reconfigure the attendant political processes of the country to better position itself to respond expeditiously to the challenges posed by the emerging regional ASEAN architecture.